Human evolution: Gradual or Punctuated? Accelerated integration of mtDNA pseudogenes into the nuclear genome coincides with speciation of the human genus. A Hypothesis. - Gunbin,Konstantin; Popadin,Konstantin; Peshkin,Leonid; Annis,Sofia; Ackermann,Rebecca; Khrapko,Konstantin (PeerJ Preprints, 2017)
The question: human evolution- gradual process or a rapid discontinuous change? Whether human origin was a gradual process or a result of rapid change has been a focus of intense debate. Of particular interest is the climate change ~2.9-2.5 Ma, thought to have precipitated the separation of the genus Homo (~2.8Ma). The debate mostly concerned continuity/punctuality of the fossil record, but of course the rate of the underlying genetic change is of ultimate interest/importance. Did hominid lineage experience an increased mutation rate when a large number of hominins emerged and eventually gave rise to the split between Australopitecus/Paranthropus and Homo? The obstacle: vague timing of conventional mutations. The difficulty in answering the above question lies in the way past mutations are timed. Conventional point mutations are assigned to specific branches of the DNA-derived phylogenetic trees. The essence of the problem is that mutations can be located within branch segments from branching point to branching point, but the exact position within the segment is principally unknown. Because the hominid DNA-derived phylogenetic tree is rather sparsely populated with branches, the precision of mutation timing is low, e.g., human-specific mutations can be positioned within ~6 My from separation from chimpanzee. The solution: NUMTs – mutations with an internal clock. NUMTs are insertions of mtDNA sequences into the nuclear genome. Unlike point mutation, each NUMTs actually represents a branch on the mtDNA phylogenic tree and thus its time of insertion can be determined as precise as their branching point can be positioned on the tree. In a sense, NUMTs are “mutations with an internal clock”, which is synchronized with the well-established mtDNA mutation evolution clock. By determining the NUMTs’ insertion time points, one can ask whether whether NUMTs were inserted at a constant rate over time or at increased rate during critical periods of evolution, according with the “punctuated evolution” model. Results: Hundreds of pseudogenes have been inserted into the human genome over the last ~60 My of which we considered the last 6 My. Various quality filters resulted in the selection of 18 NUMTs most suitable for phylogenetic analysis. Insertion times of these 18 NUMTs cluster around 2.8Ma. While timing of insertion of NUMTs is imprecise, the observation such a cluster is highly statistically significant. Discussion: It is tempting to hypothesize that accelerated insertion of NUMTs is somehow linked to the speciation process. NUMTs could be either "riders i.e., the rate of insertion could be increased by the overall higher genome flexibility during the speciation period, or "drivers", i.e. they are fixed in the population at increased rate during speciation due to increased selective pressures. If correct, the hypothesis of accelerated pseudogenization would support the idea that evolution of our genus might have been discontinuous.
Keywords: mitochondria; mtDNA; human evolution; NUMT; human origin; phylogeny; punctuated evolution